A task-dependent analysis of closed vs. open and fine vs. gross motor skills in handedness. - Marcori, Alexandre J.; Gamberini, Matheus G.; Ocklenburg, Sebastian; Monteiro, Pedro H. M.; Okazaki, Victor H. A. (Laterality, 2024)
The traditional classifications of motor skills nature (open vs closed; fine vs gross) have not been considered in handedness investigations. Instead, previous research focused on comparing complex vs less complex motor behaviour, leaving a gap in the literature. We compared manual preference between different motor skill characteristics, namely: fine and closed (FC), gross and closed (GC) and gross and open (GO) tasks. The hand preference was assessed with the Global Lateral Preference Inventory in four hundred and forty participants (244 women) aged from 18 to 59 years old. By assessing the degree and direction of handedness in different motor skills, our results showed a stronger lateralization pattern for FC motor skills as compared to GC and GO, with GO also being less lateralized than GC. Our results expand those of previous investigations that used the motor skill complexity definitions by showing how handedness can also be modulated by the interaction between classic motor skills classifications. Future research should consider fine vs. gross and open vs. closed classifications when selecting tasks for analysis of asymmetries of preference.